IMPLEMENTASI SUPERVISI KEPALA MADRASAH DALAM PENINGKATKAN PROFESIONALITAS KINERJA GURU - Ma’ruf Ishak Ola (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The principal, as the leader of an educational institution, plays a significant role in developing teachers' abilities in the learning process. To make teachers professional, it is not enough to simply improve their competence through training, coaching, or providing opportunities for further study. Other aspects must also be considered, such as improving discipline, providing motivation, and offering guidance through supervision. Therefore, the principal, as the leader of the school, must always monitor and guide teachers in their efforts to improve their professional performance. The research method used is a qualitative approach with a descriptive research type. The data collection techniques used include in-depth interviews, observation, and documentation. The data were analyzed using Miles and Huberman's interactive analysis model, which consists of data reduction, data presentation, and conclusion drawing. The validity of the data was tested through source and technique triangulation, as well as member checks to ensure the accuracy of the information obtained from the field. The conclusions of this study are (1) The principal's supervision plan to improve teacher performance at MIN 1 Flores Timur is prepared every semester and documented by the principal, (2) The implementation of madrasah principal supervision in improving the professionalism of teachers' performance at MIN 1 Flores Timur uses two techniques, namely individual and group techniques, and (3) The evaluation of madrasah principal supervision in improving the professionalism of teachers' performance at MIN 1 Flores Timur is carried out at the end of each semester with the aim of identifying the shortcomings or successes of the madrasah principal's supervision itself.